POLA KOMUNIKASI ANTARPRIBADI PELATIH DAN PEMAIN DALAM PROGRAM LATIHAN KOMUNITAS FUTSAL TUTER FC - Nilamsari, Natalina; Perdana, Mochammad Nandang (Universitas Prof. Dr. Moestopo (Beragama), 2019)
The aim of the researchers was to find out how the patterns of personal communication between coaches and players in the futsal training program at the FC Tuter futsal community and the supporting factors and inhibiting factors of existing communication activities. This research was developed using a descriptive qualitative approach. The research paradigm is a case study on the TUTER FC futsal community and the method used is positivism. The results of the analysis showed that the implementation of two-way communication patterns was considered to be the most effective in conducting training activities. It could be said to be effective because the coach delivered the material and was well received by the players. As well as providing feed back given by players to the coach shows the effectiveness of communication.